1985
DOI: 10.1177/00220345850640110401
|View full text |Cite
|
Sign up to set email alerts
|

Micro-analytical Determination of pH, Calcium, and Phosphate in Plaque Fluid

Abstract: Micro-analytical techniques for the determination of calcium, phosphate, and pH in a small volume (less than 0.25 microliter) of plaque fluid are described and evaluated. The accuracy and the precision of the techniques were compared with those for standard macrotechniques applied to a large pooled plaque fluid sample. The results obtained for the micro-analysis of pooled plaque fluid were in excellent agreement with those obtained by macromethods. The described techniques were also used to analyze plaque flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 16 publications
3
22
1
Order By: Relevance
“…This is followed by a gradual recovery to its starting value, usually over 30-60 min, although this can be longer in some individuals [34]. Therefore, it would be desirable for a specimen to quickly raise the cariogenic pH from 4.0 to 5.5 or above in order to help resist caries.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by a gradual recovery to its starting value, usually over 30-60 min, although this can be longer in some individuals [34]. Therefore, it would be desirable for a specimen to quickly raise the cariogenic pH from 4.0 to 5.5 or above in order to help resist caries.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of administering acidogenic chal lenges has not been clearly demonstrated with natural plaque, presumably because of the already high levels of Ca and Pi in the plaque fluid. Thus, Tatevossian [1987] reported no change 15 min after eating a sugar candy, although Rankine et al [1985] reported an in crease of Ca from 3.5 to 6.3 mmol/1 over the first 15 min, with no further change over the next 45 min. Pi rose in parallel from 10.1 to 14.1 mmol/1, then re turned to baseline by 60 min.…”
Section: Comparisons With Natural Plaquementioning
confidence: 97%
“…Accumulation of the mineral constituents was shown to be dependent on metabolic activity of the S. mutans plaque, and experi ments in which enamel blocks were replaced with blocks made of acrylic plastic gave Ca and Pi concentrations of 2.510.6 and 6.612.4 mmol/1, respectively, demonstrating that most of the Ca and about one-third of the Pi were derived from enamel. The data suggested, furthermore, that Ca and Pi were partially bound to complex macromolecules, and that part eventually recrystallized as mineral within the plaque.A number of investigators have reported the pres ence in natural dental plaque of relatively high con centrations of calcium and inorganic phosphate [Tatevossian and Gould, 1976; Dawes, 1984;Rankine et al, 1985;Tatevossian, 1987;Moreno and Margolis, 1988]. However, relatively little is known about the ef fects of carbohydrate challenges on these constitu ents, and it is not clear whether plaque Ca and inor ganic phosphate (Pi) are derived from enamel or sim ply reflect diffusion equilibria with the ions in saliva.…”
mentioning
confidence: 99%
“…Prior to plaque collection, all subjects refrained from oral hygiene for 48 h and fasted overnight (about 12 h). For each subgroup, pooled plaque samples were collected [Rankine et al, 1985] from designated surfaces of each subject; samples from differ ent subjects were pooled under water-saturated mineral oil contained within a single (approximately 0.01ml) microcentrifuge tube. The microcentrifuge tubes were fabricated from an ultra micropipet tip (USA Scientific, Ocala, Fla.) by melting the tip end.…”
Section: Subjectsmentioning
confidence: 99%